A systematic review on the cost‐effectiveness of the computer‐assisted orthopedic system - Hua Li; Tengfeng Zhuang; Wenrui Wu; Wenyi Gan; Chongjie Wu; Sijun Peng; Songwei Huan; Ning Liu (Wiley, 2022)
Abstract Computer‐assisted orthopedic system (CAOS) is rapidly gaining popularity in the field of precision medicine. However, the cost‐effectiveness of CAOS has not been well clarified. We performed this review to summarize and assess the cost‐effectiveness analyses (CEAs) with regard to CAOS. Publications on CEA in CAOS have been searched in PubMed and CEA Registry up to May 31, 2022. The Quality of Health Economic Studies (QHES) instrument was used to estimate the quality of studies. Relationships between qualities and potential factors were also examined. There were 15 eligible studies in the present review. Twelve studies evaluated CAOS joint arthroplasties and found that CAOS joint arthroplasties were cost‐effective compared to manual methods. Three studies focused on spinal surgery, two of which analyzed the cost‐effectiveness of CAOS for patients after spinal fusion, with conflicting results. One study demonstrated that CAOS was cost‐effective in spinal pedicle screw insertion. The mean QHES score of CEAs included was 86.1. The potential factors had no significant relationship with the quality of studies. Based on available studies, our review reflected that CAOS was cost‐effective in the field of joint arthroplasty. While in spinal surgery, the answer was unclear. Current CEAs represent high qualities, and more CEAs are required in the different disciplines of orthopedics where CAOS is employed.